1986
DOI: 10.1182/blood.v67.3.616.616
|View full text |Cite
|
Sign up to set email alerts
|

The mutual relationship between the two molecular forms of the major fibrinolysis inhibitor alpha-2-antiplasmin in blood

Abstract: Alpha-2-antiplasmin, a major inhibitor of fibrinolysis, is synthesized in the liver and occurs in blood in two molecular forms: a very active plasminogen-binding (PB) form and a less active nonplasminogen-binding (NPB) form. This study investigates the origin and mutual relationship of these two forms in vivo and in vitro. Despite wide variation in plasma concentration of the inhibitor (16% to 138%), the ratio between the two forms in vivo was found to be, in the main, constant among healthy volunteers, hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Surprisingly, approximately 40% of circulating AP binds plasmin slowly [28]. Sasaki et al [29] made the same observation and demonstrated that the slow form was truncated at the C-terminus by at least the final 26 amino acids.…”
Section: C-terminal Extensionmentioning
confidence: 89%
“…Surprisingly, approximately 40% of circulating AP binds plasmin slowly [28]. Sasaki et al [29] made the same observation and demonstrated that the slow form was truncated at the C-terminus by at least the final 26 amino acids.…”
Section: C-terminal Extensionmentioning
confidence: 89%
“…In the circulation, the α2AP protein undergoes both N‐ and C‐terminal proteolytic cleavages, which significantly modify its activity. In approximately 65% of circulating α2AP the C‐terminus is intact so it can bind to plasmin(ogen) (plasminogen‐binding α2AP, PB‐α2AP), whereas the remainder (~35%) is cleaved and loses its ability to bind plasminogen (non‐plasminogen‐binding α2AP, NPB‐α2AP) . NPB‐α2AP remains an active plasmin inhibitor, but displays very slow binding kinetics to plasmin and is not significantly crosslinked into fibrin by activated factor XIII .…”
Section: Introductionmentioning
confidence: 99%
“…The C‐terminal region is a 51 amino acid long extension that is unique among serpins and contains a secondary binding site for plasminogen and plasmin (Sugiyama et al , 1988). About 30% of plasmin inhibitor in plasma exists in a proteolytically modified form that lacks the secondary C‐terminal plasmin(ogen) binding site (Kluft et al , 1986). Plasmin inhibitor in plasma may also be proteolytically modified in the N‐terminus resulting in formation of a 12 amino acids shorter form with N‐terminal methionine (Bangert et al , 1993).…”
mentioning
confidence: 99%